(untitled) (GAIMS Journal of Medical Sciences, 2022)
Introduction: Acinetobacter species has now been identified as a prime and notorious cause of nosocomial pneumonia and bloodstream infections, which is been observed especially among immunocompromised patients with underlying co morbidities or deliberating illnesses. Globally, there has been a significant increase in resistance of this organism to most of the antimicrobials in recent period. Aim: The aim of our study is to evaluate Acinetobacter isolates obtained from various clinical samples., their antimicrobial resistance pattern and changes in resistance pattern of the organism from the samples which they have been isolated from our tertiary care hospital. Materials and Methods: In this study, Acinetobacter isolates were obtained from both the in-patients or out-patients during the period between 01.07.2021-01.07.2022 were used. The isolation and identification were done by using conventional methods. Antimicrobial susceptibility testing was done by Disc diffusion method as per CLSI guideline. Results: More than 50% of isolates were found to be resistant to carbapenems such as Meropenem (60%) and Imipenem (55%) respectively; these antibiotics were used in our test battery. The isolates had exhibited a high level of resistance to the group of β-lactam combination antibiotics namely Piperacillin-Tazobactam (90%) and almost complete resistance to cephalosporins which were used in our testing battery at our laboratory. Moreover, they showed low level of resistance to ciprofloxacin among the fluoroquinolones group. Conclusion: Our study showed high level of resistance to all available Antibiotics excluding colistin among Acinetobacter species. There has been an increased rate of complete drug-resistant isolates. In order to prevent development of multiple resistances, and produce maximum utility of the available limited antibiotic resources, each laboratory should determine the percentage of resistance to various Antibiotics among Acinetobacter species in different geographical region.